Interrelationship between Rainfall Index and Nifty Index: An Empirical Study - N, Dileep; Kotreshwar, G. (Gyan Management Journal, 2022)
The proposed study is an attempt to determine whether a relationship  exists between rainfall index and NSE Nifty index. The study used the  monthly mean rainfall data and monthly closing price of Nifty index. The  study applied Augmented Dickey-Fuller (ADF) test, correlation analysis,  the GARCH (1,1) model, and the Granger Causality test to analyse the  interrelationship. The results of correlation matrix show that there is no  interrelationship between the two variables. The GARCH (1,1) model found  that the NSE Nifty index is not affected by the rainfall index and Granger  Causality test displays that rainfall index does not Granger Cause the Nifty  index. According to the authors’ knowledge, this is the first empirical study  to determine the interrelationship between the rainfall index and the Nifty  Index over a longer period of time.
Keywords: Rainfall index; NSE Nifty index; GARCH (1,1) model; Granger Causality test and Distinct asset